2007
DOI: 10.1037/0097-7403.33.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Remembrance of places you passed: Social spatial working memory in rats.

Abstract: Pairs of rats were tested in a radial-arm maze to determine whether the spatial choices made by one rat affect the subsequent spatial choices of the other rat. In a free-choice procedure, rats showed an increased tendency to choose the location that had most recently been chosen by a foraging partner but a decreased tendency to visit locations that the foraging partner had visited earlier. Forced-choice procedures were used to better control the social stimulus and the interactions between the rats. Under some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
58
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 42 publications
8
58
1
Order By: Relevance
“…Reports from our laboratory have explained the tendency of a rat to choose maze arms in the radial maze that were visited earlier by a foraging partner in terms of an influence of the foraging partner on choices made by the focal rat (Brown et al, 2007;Brown et al, 2008). However, an alternative possibility is that the tendency to visit the most recent location chosen by the other rat is an artifact of common preferences for particular maze arms.…”
Section: Methodsmentioning
confidence: 85%
See 4 more Smart Citations
“…Reports from our laboratory have explained the tendency of a rat to choose maze arms in the radial maze that were visited earlier by a foraging partner in terms of an influence of the foraging partner on choices made by the focal rat (Brown et al, 2007;Brown et al, 2008). However, an alternative possibility is that the tendency to visit the most recent location chosen by the other rat is an artifact of common preferences for particular maze arms.…”
Section: Methodsmentioning
confidence: 85%
“…Recently, work in our laboratory has shown that rats foraging together with their cagemate in a radial-arm maze are also affected by the choices of the other rat and that at least some of these effects are produced by memory for the choices made earlier during the trial by the other rat (Brown, Farley, & Lorek, 2007;Brown et al, 2008). The nature of the effect produced by choices of the other rat is sometimes an increase in the tendency to visit the locations chosen by it and sometimes an opposite tendency to avoid visits to those locations.…”
mentioning
confidence: 99%
See 3 more Smart Citations